ESTIMATION OF MEASUREMENT UNCERTAINTY IN THE DETERMINATION OF Fe CONTENT IN POWDERED TONIC FOOD DRINK USING GRAPHITE FURNACE ATOMIC ABSORPTION SPECTROMETRY - Harry Budiman; Fransiska Sri H; Krismastuti Krismastuti; Nuryatini Nuryatini (Indonesian Journal of Chemistry, 2009)
The evaluation of uncertainty measurement in the determination of Fe content in powdered tonic food drink using graphite furnace atomic absorption spectrometry was carried out. The specification of measurand, source of uncertainty, standard uncertainty, combined uncertainty and expanded uncertainty from this measurement were evaluated and accounted. The measurement result showed that the Fe content in powdered tonic food drink sample was 569.32 µg/5g, with the expanded uncertainty measurement ± 178.20 µg/5g (coverage factor, k = 2, at confidende level 95%). The calibration curve gave the major contribution to the uncertainty of the final results.